The Relathionship Between Exclusive Breatfeeding and The Nutritional Status of Infants Aged 0-6 Months in Mertoyudan Health Center 2 - Amelia, Tarisa Ayu; Wardani, Septi; Mareta, Reni (Prosiding University Research Colloquium, 2022)
Malnutrition in children is a pulic health problem that is still a priority by the goverments. From Riskesdas 2018 shows 30,8% children under five are malnutrourised. One of the factors related to nutritional status is exclusive breastfeeding, where breastmik contains the best nutrients for children growth. Research purpose this study aims to determine the relationship between exclusive breastfeeding and the nutritional status of infants aged 0-6 months in the working area of Mertoyudan 2 Public Health Center. Methods This study used analytic observational method with crosssectional approach. The sample are mothers who have babies or toddlers as many as 88 respondents with proportional random sampling technique. Data analysis was carried out with the Spearman test.Result The result showed that there was a significat relationship between exclusive breastfeeding and the nutritional status og the baby with p value= 0,000 It can be concluded that there is a relationship between exclusive breatfeeding and the nutritional status of infants aged 0-6 months in the working area of Mertoyudan 2 Public Health Center.